1977
DOI: 10.1177/25.4.323352
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal gold, a useful marker for transmission and scanning electron microscopy.

Abstract: Electron dense markers of a size suitable for transmission electron microscopy and scanning electron microscopy have been prepared with gold granules labeled with a monolayer of specific macromolecules. The optimum conditions for preparing the markers have been ascertained. The method is simple, rapid and seems to be general since gold granules have been labeled with polysaccharides and proteins. As homogeneous populations of gold granules having different sizes can be prepared, the method is also suitable for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
209
0
3

Year Published

1980
1980
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 608 publications
(216 citation statements)
references
References 22 publications
0
209
0
3
Order By: Relevance
“…Because of its low molecular weight, WGA (from SIGMA) was crosslinked to Bovine Serum Albumin (BSA) with glutaraldehyde, as suggested by Horisberger and Rosset [16]. The optimal amount of WGA-BSA solution necessary to obtain the labelling solution was determined, with NaCl to flocculate, according to Faulk and Taylor [6].…”
Section: Wga-gold Labelling Of Chitinmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its low molecular weight, WGA (from SIGMA) was crosslinked to Bovine Serum Albumin (BSA) with glutaraldehyde, as suggested by Horisberger and Rosset [16]. The optimal amount of WGA-BSA solution necessary to obtain the labelling solution was determined, with NaCl to flocculate, according to Faulk and Taylor [6].…”
Section: Wga-gold Labelling Of Chitinmentioning
confidence: 99%
“…Adjusted by Horisberger and Rosset [15,16], this direct and acute method was used for the localization of chitin in many tissue sections and in unicellular organisms, such as the yeasts Saccharomyces cerevisiae and Candida utilis [17], and in cysts produced by the Rhizopod Entamoeba invadens [1]. We applied this treatment for the first time in a ciliate cyst, as announced in a preliminary note [30].…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed that several lectins are useful Tsuyama et al to label the compartment of the Golgi apparatus and/or mucous granules (25-27, 35). Moreover, lectins labeled with colloidal gold are a better probe to study the intracellular glycosylation sites especially in relation to the Golgi apparatus (13,14,28). The epithelial cells of the colonic crypt in the rat proximal colon proliferate at the branching point of the crypt.…”
mentioning
confidence: 99%
“…The amount of secondary antibodies needed to saturate GNP surface was experimentally determined through incubating a fixed volume of the GNP preparation with increasing quantity of Ab rab and observing aggregation when 10% NaCl was added (the aggregation determined a color shift of GNPs from brilliant red to purple-blue). The saturating condition was judged as the lower antibody amount that prevented aggregation [35]. The amount of Ab rab able to completely cover GNP surface was also theoretically calculated as the ratio between the total surface area of GNPs and the size of an antibody molecule [30].…”
Section: Optimization Of the Silver Enhanced Lateral Flow Immunoassaymentioning
confidence: 99%